Bank Rakyat Indonesia’s Mobile Banking Services Customers in Jember Sub-Branch Office: Bank Rakyat Indonesia’s Mobile Banking Services Customers in Jember Sub-Branch Office - billah, tsiqoh billah (Archives of Business Research, 2020)
This study is a qualitative study aimed at explaining Bank Rakyat Indonesia’s mobile banking (m-Banking) services the Jember Sub-Branch Office and to find out BRI’s strategy in improving m-Banking service as a reliable product for customers. The progress of the business system with the e-commerce system makes consumers switch ways by using non-cash payment methods (cashless). Technological advancements in the banking sector have encouraged the banking sector to be more innovative in providing non-cash payment services in the form of a transfer system and payment instruments in the form of electronic card, because they are secure, fast, efficient, and global. The study found that there are obstacles, namely an easy network error so that transactions can be hampered, high SMS costs for business people, can be easily accessed by others if customers forget to log off. The conclusions of using the TASS (Trust, Accuracy, Speed, Scurity) method from these five aspects are scurity and speed that need to be considered by the BRI bank, because the are several case of cyber crime and old repairs / maintence.